2019 Kansas State University Industrial Hemp CBD Variety Trial - Jason Griffin; Michael J. Shelton; Clint Wilson; Tami Myers (Kansas Agricultural Experiment Station Research Reports, 2020)
Hemp is a broad term used to describe the many varieties ofCannabissativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently allowed to be grown again in the United States. Varieties have been selected and are currently grown with a wide range of cannabinoid profiles. Cannabinoids are of interest for their putative medical and therapeutic role in humans and pets. Cannabidiol (CBD) and THC are the two cannabinoids of primary interest. THC is of interest because it determines whether the final product is considered hemp (0.3% THC). CBD is of interest because of its potential therapeutic properties and its legal status across many states. Currently, there is no information available regarding adaptability or cannabinoid production of these varieties in Kansas. In 2019, Kansans were allowed to apply for research licenses to grow industrial hemp. It was assumed the crop would grow well throughout Kansas since there are wild remnant populations ofC. sativaflourishing at numerous locations across the state. However, controlled variety trials are necessary to determine which varieties are best adapted to Kansas. Currently, growers must rely on information generated from other states with vastly different growing conditions than Kansas. Variety selection is vital in CBD hemp production considering that environmental conditions strongly influence cannabinoid ratios and ultimately, total cannabinoid content. The objective of this study was to evaluate commercially available varieties of CBD hemp in south-central Kansas grown in containers outdoors or inside of a high tunnel. Outdoor hemp production is of interest because of reduced infrastructure cost. However, pollination is a concern with outdoor hemp. Unpollinated female flowers contain the highest concentration of cannabinoids. When flowers are pollinated and seeds are produced, the total concentration of all cannabinoids is greatly diminished. In Kansas, naturalized populations ofC. sativacan be found throughout the state. With pollen easily traveling as far as 3 miles there is concern regarding the viability of outdoor CBD hemp potential. We wanted to test whether a covered high tunnel could effectively reduce pollination of the plants within.
Keywords: alternative crops; specialty crops; cannabidiol; tetrahydrocannabinol; THC; essential oils; high tunnel